2012
DOI: 10.4103/2319-4170.106150
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing aesthetic and functional outcomes at donor sites

Abstract: In recent years, there has been increasing interest by reconstructive surgeons in improving the aesthetic and functional outcomes of donor sites. As the success rate of free tissue transfers has exceeded more than 95% in most microsurgical centers, more emphasis can be shifted to the donor site. However, morbidities of donor sites can occur not only in free tissue transfers, but in locoregional flaps as well. In reconstructive procedures, the main principle is to mobilize normal tissue and utilize it to recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…In this modern era of reconstructive surgery, we should strive to improve outcomes not only at the recipient site but also at the donor site. [35][36][37] In a study previously performed at our institution, we demonstrated that it was possible to directly close the ALT donor-site defects that were less than 16% of the thigh circumference. 19 With this in mind, in five patients for whom a wide skin paddle was required, we adopted the principle of designing the ALT flap based on two sizable perforators.…”
Section: Discussionmentioning
confidence: 81%
“…In this modern era of reconstructive surgery, we should strive to improve outcomes not only at the recipient site but also at the donor site. [35][36][37] In a study previously performed at our institution, we demonstrated that it was possible to directly close the ALT donor-site defects that were less than 16% of the thigh circumference. 19 With this in mind, in five patients for whom a wide skin paddle was required, we adopted the principle of designing the ALT flap based on two sizable perforators.…”
Section: Discussionmentioning
confidence: 81%
“…This significant percentage of patients can still endure donor-site morbidities, mostly resulting in the need for additional skin grafting. [ 6 , 15 ] However, with the development of reconstructive techniques, better reconstruction and restoration can be achieved not only at the recipient site but also at the donor site. [ 12 ] In our study, a variety of surgical techniques were used to accomplish direct closure of the donor site, resulting in a cosmetic and functional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that more than 80% of donor sites of the ALT flap can be closed primarily, 9 a significant percentage of patients still suffer donor-site morbidities, mainly resulting from skin grafting. In this modern era of reconstructive surgery, however, we should strive to improve outcomes not only at the recipient site but also at the donor site.…”
Section: Discussionmentioning
confidence: 99%
“…This reduces the effective width of the donor site, thus allowing for direct primary closure. 9 Indeed, the reliability of reverse flow to nourish an ALT skin paddle is well established, 12 and this can be used when planning retrograde V-Y advancement flaps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation